The Role of ChatGPT in Improving the Efficiency of Education Management Processes - Hegar Harini (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Education is one of the main pillars in a country's development, given its important role in shaping a competent and competitive young generation. In today's digital and information technology era, the role of technology in education is increasingly important to improve the efficiency and effectiveness of the learning process and overall education management. The purpose of this study is to examine more deeply the role of ChatGPT in improving the efficiency of the education management process. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The research found that ChatGPT's role in improving the efficiency of the education management process is significant. This technology has opened the door for a positive transformation in the way education is managed, taught and run. By providing instant information, assistance in learning, and support in communication, ChatGPT can enrich the educational experience of students, teachers, parents, and administrative staff.